2013
DOI: 10.1371/journal.pone.0069240
|View full text |Cite
|
Sign up to set email alerts
|

Berberine Targets AP-2/hTERT, NF-κB/COX-2, HIF-1α/VEGF and Cytochrome-c/Caspase Signaling to Suppress Human Cancer Cell Growth

Abstract: Berberine (BBR), an isoquinoline derivative alkaloid isolated from Chinese herbs, has a long history of uses for the treatment of multiple diseases, including cancers. However, the precise mechanisms of actions of BBR in human lung cancer cells remain unclear. In this study, we investigated the molecular mechanisms by which BBR inhibits cell growth in human non-small-cell lung cancer (NSCLC) cells. Treatment with BBR promoted cell morphology change, inhibited cell migration, proliferation and colony formation,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
69
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(74 citation statements)
references
References 45 publications
3
69
0
Order By: Relevance
“…Berberine has been reported to inhibit topoisomerase II enzyme in vitro [54]. The other possibility of berberine-induced cell killing seems to be due to the trans activation of nuclear factor-κB (NF-κB), and cyclo-oxygenase II, and suppression of activator protein 1, cyclins, Akt, p53 and PARP and induction apoptosis [37,40,[55][56][57][58].…”
Section: Discussionmentioning
confidence: 99%
“…Berberine has been reported to inhibit topoisomerase II enzyme in vitro [54]. The other possibility of berberine-induced cell killing seems to be due to the trans activation of nuclear factor-κB (NF-κB), and cyclo-oxygenase II, and suppression of activator protein 1, cyclins, Akt, p53 and PARP and induction apoptosis [37,40,[55][56][57][58].…”
Section: Discussionmentioning
confidence: 99%
“…The present study detected VEGF, PEDF, Cox-2, AKT, p-AKT, E-cadherin, RhoA and RhoC, which are associated with tumor apoptosis, growth, invasion and metastasis (18)(19)(20). The results revealed that the expression of all the above factors was increased or decreased when shET-1 and Endostar were present or absent.…”
Section: Discussionmentioning
confidence: 51%
“…12B). Recently, Fu et al demonstrated that berberine inhibited human nonsmall cell lung cancer cell growth by simultaneously targeting NF-κB/COX-2, PI3K/Akt and caspase signalling pathways (58). Furthermore, others studies showed an antitumor effect of berberine via inhibition of NK-κB pathway and induction of apoptosis (59,60).…”
Section: Resultsmentioning
confidence: 99%